An exploratory study of the educational processes of the PhD - Wan, CD (2015)
There has been a significant increase in the numbers of students undertaking doctoral study over the last 20-30 years. This means that the PhD is no longer solely an elite degree designed to prepare graduates for an academic career. Instead, emphasis has increasingly been placed on the role of the PhD in producing 'advanced knowledge workers' who are expected to make a contribution to the production of knowledge in a knowledge-driven economy. This has led to an increased focus on the educational dimension of the PhD and the educational processes involved in developing students to become researchers in a range of contexts. However, the educational processes involved in the PhD are complex and differ across higher education systems, institutions and disciplines. They include formal and informal activities and involve a large number of actors with different expectations about the aims and outcomes. This study aims to gain an in-depth understanding of the educational processes of the PhD by exploring the complexity underlying these processes. The research was based on case studies in six departments. The case studies focused on the PhD processes of the six departments from three disciplines in four higher education institutions in England. Interviews with PhD Programme Directors, supervisors and students were complemented by analysis of institutional and departmental documents. The research was guided by a multi-level framework to examine the institutional, departmental, interpersonal and individual levels, and the inter-relatedness between levels. As such rich narratives provide insight into factors such as the PhD thesis and its influence on the supervisory relationship, formal initiatives such as assessment and coursework, and the Skills Training Programme and its underlying notion of employability. Three forms of complexity were identified. The first relates to the fact that the educational processes are individualistic in nature, and there is a need to understand the influences of the personal, social, educational and professional domains of the individual students and supervisors independently and collectively in shaping these complex processes. The second underlines the tensions and potential contradictions within and between actors as a result of the interpretation and implementation of these processes across the four levels. The third concerns a tension between the need for these processes to remain individualistic and the pressure for departments and institutions to provide standardised processes for all students. By identifying and gaining a greater understanding of these complexities, this research contributes to a more comprehensive understanding of the educational processes of the PhD based on grounded empirical evidence. This understanding is important in developments for enhancing the quality of PhD education, and in developing programmes which support students to become researchers in a range of different employment contexts.